Manajemen Asesmen Sumatif Akhir Semester Berbasis Aktivitas Menyenangkan - Isnayah, Magfirah; Inganah, Siti; Mahmudah, Rafiah (Universitas Sebelas Maret, 2026)
This study aims to describe the management of enjoyable activity-based final semester summative assessments at RA Nailul Huda, which includes the stages of planning, implementation, evaluation, and follow-up. The study uses a qualitative approach with a descriptive type. The research subjects consisted of the head of RA, classroom teachers, parents, and students. Data collection techniques were carried out through observation, semi-structured interviews, and documentation, while data analysis referred to the Miles and Huberman model through the stages of data reduction, data presentation, and conclusion drawing. The results showed that assessment planning was carried out systematically by determining aspects of child development, designing play activities, developing authentic assessment instruments, and arranging child-friendly time and facilities. The assessment was carried out in a variety of fun and flexible play activities so that children could demonstrate their abilities naturally without pressure. Evaluation and follow-up were carried out through comprehensive processing of child development data, narrative reporting to parents, teacher reflection, and adjustment of learning according to children's needs. This study concluded that summative assessment based on enjoyable activities can be an effective strategy in supporting holistic, meaningful assessment that is in line with the characteristics of early childhood education